The Effects of Biogeotextiles on the Stabilization of Roadside Slopes in Lithuania - Benediktas Jankauskas; Genovaitė Jankauskienė; Michael Augustine Fullen; Colin Antony Booth (The Baltic Journal of Road and Bridge Engineering)
Biogeotextiles constructed from the leaves of Borassus aethiopum and Mauritia flexuosa are investigated at the Kaltinėnai Research Station of the Lithuanian Institute of Agriculture, which is participating in the EU-funded BORASSUS Project. Biogeotextiles are potentially excellent biodegradable and environmentally-friendly materials useful for soil conservation. Field studies on a steep (21–25°) roadside slope in Lithuania suggest biogeotextile mats are an effective and sustainable soil conservation technique. Biogeotextiles have a potential as a biotechnical soil conservation method for slope stabilization and protection from water erosion on steep industrial slopes and may be integrated with the use of perennial grasses to optimize protection from water erosion. The investigations demonstrated that a cover of Borassus and Buriti mats improved the germination and growth of sown perennial grasses. The biomass of perennial grasses increased by 52.0–63.4% under cover of Borassus mats and by 18.6–28.2% under cover of Buriti mats. Over 2 years, the biogeotextiles (Borassus and Buruti, respectively) decreased soil losses from bare fallow soil by 90.8% and 81.5% and from plots covered by perennial grasses by 87.9% and 79.0%, respectively.